Control of primary metabolism in plants - Plaxton, William C (Blackwell, 2012)
Focuses on the pathways of plant primary metabolism and their control Emphasises the multi--layers of control -- from transcriptional, through to translational and post--translational Takes account of the impact of genomics and proteomics on the subject